ETHICAL ASPECTS OF ORGAN TRANSPLANTATION AND TRANSPLANTATION TOURISM - Peličić, Damir (HEALTH CARE, 2024)
Modern medicine and technology have advanced significantly since the mid-twentieth century, but transplant medicine is still a hotly debated topic, both medically and religiously, legally and ethically. In order to carry out an organ transplant, whether it is related, unrelated or cadaveric transplantation, a number of conditions must be met in order to adequately prepare the patient and the potential donor. For this review, we used relevant literary data using databases such as: PubMed, SCOPUS, Serbian Citation Index, etc. All publications related to ethical principles and legal aspects of transplantation and organ donation, both in the world and in Montenegro. We referred to the Istanbul Declaration, which was also signed by Montenegro.
Keywords: Organ donation, Istanbul Declaration, transplantation, religion, ethics